DETEKSI DINI DAN PENCEGAHAN GANGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIF (GPPH) PADA ANAK TK ‘AISYIYAH BUSTANUL ATHFAL (ABA) PURBAYAN KOTAGEDE YOGYAKARTA - Lailatuz Zaidah; Dwi Yuningsih (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Community Service has been carried out in September 2024 regarding early detection and prevention of attention deficit disorders that have been implemented at TK 'Aisyiyah Bustanul Athfal (ABA) Purbayan Kotagede Yogyakarta, this activity was carried out with the aim of increasing parents' understanding in detecting attention deficit disorders in children, and is a joint effort between lecturers and schools along with parents in order to realize community concern, awareness, understanding and skills in detecting attention deficit disorders and hyperactivity (GPPH). The government plays an active role in the detection, stimulation, and intervention of child growth and development through several programs such as the Early Detection of Growth and Development (DDTK) program to detect child development early on, the SDIDTK program for stimulation and intervention, and related policies to support the implementation of these programs. These activities are part of promotive, preventive and community empowerment efforts in preventing attention deficit disorders and hyperactivity (GPPH). This community service activity is carried out through socialization/workshops using lecture methods, discussions and training on how to examine attention deficit disorders and hyperactivity in children. The results of the community service show that the understanding of school teachers and parents has increased in detecting the development of attention span.